1993
DOI: 10.1002/j.1460-2075.1993.tb06220.x
|View full text |Cite
|
Sign up to set email alerts
|

The Schizosaccharomyces pombe cwg2+ gene codes for the beta subunit of a geranylgeranyltransferase type I required for beta-glucan synthesis.

Abstract: The product of the Schizosaccharomyces pombe cwg2+ gene is involved in the biosynthesis of beta‐D‐glucan. When grown at the non‐permissive temperature, cwg2‐1 mutant cells lyse in the absence of an osmotic stabilizer and display a reduced (1‐3) beta‐D‐glucan content and (1‐3) beta‐D‐glucan synthase activity. The cwg2+ gene was cloned by the rescue of the cwg2‐1 mutant phenotype using an S. pombe genomic library and subsequently verified by integration of the appropriate insert into the S. pombe genome. Determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
63
0
1

Year Published

1996
1996
2005
2005

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(64 citation statements)
references
References 53 publications
0
63
0
1
Order By: Relevance
“…S. pombe cwg2 -(PGGT-I␤ mutant) cells are defective in ␤-D-glucan synthesis and can be rescued when grown at 37°C in high osmotic pressure media (55). In contrast, PFT␤ loss-of-function mutants are viable in yeast and Arabidopsis, possibly due to partial compensation by PGGT-I.…”
Section: Discussionmentioning
confidence: 99%
“…S. pombe cwg2 -(PGGT-I␤ mutant) cells are defective in ␤-D-glucan synthesis and can be rescued when grown at 37°C in high osmotic pressure media (55). In contrast, PFT␤ loss-of-function mutants are viable in yeast and Arabidopsis, possibly due to partial compensation by PGGT-I.…”
Section: Discussionmentioning
confidence: 99%
“…plp mutants and era1 ggb double mutants are viable and fertile). In contrast, Saccharomyces cerevisiae, Schizosaccharomyces pombe, and Drosophila melanogaster require PFT and/or PGGT I for survival (Ohya et al, 1991Diaz et al, 1993;Trueblood et al, 1993;Therrien et al, 1995). Thus, plants are unusual in their ability to survive and reproduce without PFT or PGGT I.…”
Section: Auxin Signaling In Ggb Mutant Linesmentioning
confidence: 99%
“…Analysis using GFP-Rho1 and GFPRho1C199S showed that Rho1 is localized to the cell periphery and to the septum, where the cell wall is newly synthesized, and that the C-terminal Cys is necessary for this localization. It has been reported that the cwg2 þ gene, which encodes the b subunit of a geranylgeranyltransferase type I, is required for b-glucan synthesis (Diaz et al 1993). cwg2-1 mutant cells have a swollen shape and tend to lyse at restrictive temperatures in the absence of osmotic stabilizers.…”
Section: The Membrane-bound Form Of Rho1 Functions In Cell Wall Synthmentioning
confidence: 99%